Cocoa gene bank in Trinidad - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A non-repayable grant of 2,624,000 ECU was recently made by the European Development Fund, to the Cocoa Research Unit (CRU) for a Community proqramme. This project, which is based in the Caribbean, involves the ACP countries which produce cocoa. The...